Solve x² + 5x + 6 = 0 Posted on October 23, 2021 By Littlemrslazy 12 Comments on Solve x² + 5x + 6 = 0 Solve x² + 5x + 6 = 0 Mathematics

typically if you want , you would actually put questions here for us to you. but hey, that's just me. maybe someone will magically answer the questions for you without knowing what they are.Reply

x=-2 x=-3Step-by-step explanation:x²+5x+6=0FactorWhat 2 numbers multiply to 6 and add to 52*3 =62+3 =6(x+2)(x+3) =0Using the zero product propertyx+2 =0 x+3 =0x=-2 x=-3Reply

Step-by-step explanation:The solutions arex=2,x=3Explanation:x2−5x+6=0Here we can first factorise the expression and then find the solution:Factorising by splitting middle termx2−2x−3x+6=0x(x−2)−3(x−2)=0(x−2)(x−3)=0Equating the two factors with zero to obtain solutions:x−2=0,x=2x−3=0,x=3Reply

x = - 3x = - 2Step-by-step explanation:x² + 5x + 6 = 0x² + 2x + 3x + 6 = 0x(x + 2) + 3(x + 2) = 0(x + 3) (x + 2) = 0x + 3 = 0 or x + 2 = 0x = - 3 or x = - 2-TheUnknownScientistReply

x = -2x= -3Step-by-step explanation:x 2+5x+6=0To solve the equation, factor x^2+5x+6 using formula x^2+(a+b)x+ab=(x+a)(x+b). To find a and b, set up a system to be solved.a+b=5ab=6Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 6.1,62,3Calculate the sum for each pair.1+6=72+3=5The solution is the pair that gives sum 5.a=2b=3Rewrite factored expression (x+a)(x+b) using the obtained values.(x+2)(x+3)To find equation solutions, solve x+2=0 and x+3=0.x=−2x=−3Reply

What 2 numbes multiply go get 6 and add to get -5-6 and 1(x-6)(x+1)=0set to zerox-6=0x=6x+1=0x=-1last oneReply

typically if you want , you would actually put questions here for us to you. but hey, that's just me. maybe someone will magically answer the questions for you without knowing what they are.

x=-2 x=-3

Step-by-step explanation:

x²+5x+6=0

Factor

What 2 numbers multiply to 6 and add to 5

2*3 =6

2+3 =6

(x+2)(x+3) =0

Using the zero product property

x+2 =0 x+3 =0

x=-2 x=-3

Step-by-step explanation:

The solutions are

x=2,x=3

Explanation:

x2−5x+6=0

Here we can first factorise the expression and then find the solution:

Factorising by splitting middle term

x2−2x−3x+6=0x(x−2)−3(x−2)=0(x−2)(x−3)=0

Equating the two factors with zero to obtain solutions:

x−2=0,x=2x−3=0,x=3

X+5x+6=0

x+5x=6x

6x+6=0

-6 -6

6x=-6

\6. /6

x= -1

so the answer would be -1

Answer (there are two solutions):

x = -3x = -2

I hope this helps!

x = - 3

x = - 2

Step-by-step explanation:

x² + 5x + 6 = 0

x² + 2x + 3x + 6 = 0

x(x + 2) + 3(x + 2) = 0

(x + 3) (x + 2) = 0

x + 3 = 0 or x + 2 = 0

x = - 3 or x = - 2

-TheUnknownScientist

x = -2

x= -3

Step-by-step explanation:

x 2+5x+6=0

To solve the equation, factor x^2+5x+6 using formula x^2+(a+b)x+ab=(x+a)(x+b). To find a and b, set up a system to be solved.

a+b=5

ab=6

Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 6.

1,6

2,3

Calculate the sum for each pair.

1+6=7

2+3=5

The solution is the pair that gives sum 5.

a=2

b=3

Rewrite factored expression (x+a)(x+b) using the obtained values.

(x+2)(x+3)

To find equation solutions, solve x+2=0 and x+3=0.

x=−2

x=−3

x = 2, x = 3

Step-by-step explanation:

Factorization by splitting middle term.

Hope this helped!

x + 5x + 6

x + 3x + 2x +6

x(1 + 3) + 2(x + 3)

(x + 3) (x+2) = 0

x = -3 (or) x = -2

The solution to X^2-5x+6=0

Is that x=3,2

The answer would be (c)

What 2 numbes multiply go get 6 and add to get -5

-6 and 1

(x-6)(x+1)=0

set to zero

x-6=0

x=6

x+1=0

x=-1

last one